1997
DOI: 10.1093/nar/25.8.1537
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of the DNA Hairpin d(ATCCTA-GTTA-TAGGAT): Formation of a G-A Base Pair in the Loop

Abstract: The three-dimensional structure of the hairpin formed by d(ATCCTA-GTTA-TAGGAT) has been determined by means of two-dimensional NMR studies, distance geometry and molecular dynamics calculations. The first and the last residues of the tetraloop of this hairpin form a sheared G-A base pair on top of the six Watson-Crick base pairs in the stem. The glycosidic torsion angles of the guanine and adenine residues in the G-A base pair reside in the anti and high- anti domain ( approximately -60 degrees ) respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 37 publications
6
47
0
Order By: Relevance
“…A repulsive Morse potential (39) was added to model fluctuation-driven compression of the stem helix (i.e., negative extension), and the energy associated with stretching the fully unfolded state was included, using a WLC approximation. We then subtracted the mechanical work performed by the trap on the hairpin during unfolding, calculating the extension of the partially unzipped hairpin from previous FEC measurements of ssDNA (33) but taking into account the finite width of the stem helix as measured from NMR structures (40). Finally, we incorporated the effect of thermal fluctuations in the extension of the partially unzipped hairpin by smoothing the energy landscape by an amount proportional to the ssDNA stiffness, estimated by a WLC approximation.…”
Section: Resultsmentioning
confidence: 99%
“…A repulsive Morse potential (39) was added to model fluctuation-driven compression of the stem helix (i.e., negative extension), and the energy associated with stretching the fully unfolded state was included, using a WLC approximation. We then subtracted the mechanical work performed by the trap on the hairpin during unfolding, calculating the extension of the partially unzipped hairpin from previous FEC measurements of ssDNA (33) but taking into account the finite width of the stem helix as measured from NMR structures (40). Finally, we incorporated the effect of thermal fluctuations in the extension of the partially unzipped hairpin by smoothing the energy landscape by an amount proportional to the ssDNA stiffness, estimated by a WLC approximation.…”
Section: Resultsmentioning
confidence: 99%
“…1a). The native structure of this hairpin was obtained from NMR measurements (protein data bank entry 1AC7), [35,36] except for a point mutation in which the adenine at position 10 was replaced with a cytosine. The hairpin was chosen to enable comparison of the KIS model predictions with MD simulations (see below) starting from this NMR structure.…”
Section: Application Of the Modelmentioning
confidence: 99%
“…1,2 Recently, an increasing number of studies were reported on DNA hairpins comprising a two-residue loop (or minihairpin) [3][4][5][6][7][8][9][10][11] or even a one-residue loop. [12][13][14][15] In fact, it seems that DNA preferably adopts small hairpin loops whenever possible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a reduction of the space required to fit in the closing base pair is another way to remove steric strain in the loop. This is the reason why noncanonical base pairs like a G-A, 11 a wobble T-T, 9,16,17 a Hoogsteen T-A, 18 and a G(syn)-C ϩ10 closing base pair can effectively stabilize tight hairpin loops with the aid of their unusual base pairing schemes consisting of a reduced intrastrand C1Ј-C1Ј distance compared to that in canonical Watson-Crick base pairs. In our terminology a minihairpin is defined as a two-residue loop, in which the bases closing the loop lie in an approximately planar geometry and are connected by at least one hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation